(untitled) (Indian Journal of Arid Horticulture, 2025)
In the present experiment, different physiological and biochemical parameters of ber infected with Pestalotiopsis fruit rot were studied. The sites of inoculation of ber fruits were tested and the inoculation at epicarp surface was found most sensitive and showing maximum severity of Pestalotiopsis rot. The mature and ripe stage inoculated fruits exhibited maximum severity. Changes in biochemical activity indicated that the level of total soluble solids, acidity, ascorbic acid and phenols in healthy ripe and semi-ripe ber fruits were higher as compared to infected ripe and semi-ripe fruits. The total soluble solids in inoculated semi- ripe fruits was significantly lower than uninoculated semi-ripe fruits and inoculated ripe fruits, it was lower than uninoculated ripe fruits. The level of acidity in the inoculated ripe and semi-ripe ber fruits was significantly reduced than uninoculated ripe and semi- ripe fruits. The level of ascorbic acid in inoculated ripe and semi-ripe fruits was significantly low over control. The healthy fruits (semi-ripe stage) of ber had much larger amount of ascorbic acid as compared to the diseased fruits. The activity of total phenols was higher in healthy and diseased semi-ripe fruits (0.62 and 0.48 mg/100 gm fruits) as compared to healthy ripe and diseased ripe fruits (0.52 and 0.19 mg/100 gm fruits), respectively.